1995
DOI: 10.1007/bf01705409
|View full text |Cite
|
Sign up to set email alerts
|

Different ventilatory approaches to keep the lung open

Abstract: Neither the rapid frequency modes nor the low frequency volume-controlled mode kept the surfactant deficient lungs open. Pressure-controlled inverse ratio ventilation (20 bpm) kept the lungs open at reduced end-inspiratory airway pressures and hence reduced risk of barotrauma. Reducing I:E ratio in this latter modality from 2:1 to 1.5:1 further improved oxygen delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 32 publications
0
21
0
3
Order By: Relevance
“…Higher levels of plateau pressure were not reported, so it is possible that greater aeration may have occurred at even higher pressures. A study of saline-lavaged pigs showed that 10 min of ventilation with a plateau pressure of 55 cm H 2 O was required to achieve full aeration of the lungs on CT scan after previous collapse, whereas aeration could be maintained after this with lower levels of peak and mean airway pressure (23). A recent study of patients with ARDS showed that after expiration to ambient pressure, recruitment during a slow inflation continued up to a pressure of at least 30 cm H 2 O (11).…”
Section: Limitations Of the Modelmentioning
confidence: 98%
“…Higher levels of plateau pressure were not reported, so it is possible that greater aeration may have occurred at even higher pressures. A study of saline-lavaged pigs showed that 10 min of ventilation with a plateau pressure of 55 cm H 2 O was required to achieve full aeration of the lungs on CT scan after previous collapse, whereas aeration could be maintained after this with lower levels of peak and mean airway pressure (23). A recent study of patients with ARDS showed that after expiration to ambient pressure, recruitment during a slow inflation continued up to a pressure of at least 30 cm H 2 O (11).…”
Section: Limitations Of the Modelmentioning
confidence: 98%
“…The "open lung" concept was presented in an editorial of 1992 [27,28], and proposed a treatment strategy to open up the lung with high inspiratory pressures during a short period of time and the keep the lung open with sufficient PEEP-levels afterwards. The goal was to optimise functional residual capacity (FRC) and prevent athelectasis and hence reduce stress from repetitive alveolar collapse during tidal volume variations [28][29][30]. Disconnection and suctioning induced lung collapse stand in contrast to these concepts.…”
Section: Lung Protective Ventilationmentioning
confidence: 99%
“…An experimental model of acute lung injury (ALI) was established by repeated bronchoalveolar lavage (BAL) with body warm saline of 9 mg/ml, 30 ml/kg in each wash, resulting in surfactant depletion and lung tissue prone to collapse [30,83,84]. Total amount of saline ranged 6-14 l. During the procedure the animals were ventilated with pressure (II) -or volume (III) controlled ventilation (PCV or VCV) at a tidal volume of 10 ml/kg, respiratory rate (RR) 20 breaths/min, FiO 2 1.0 and positive end expiratory pressure (PEEP) of 5-15 cmH 2 O. BAL was continued until there were no visual signs of surfactant in the fluid exchanged from the lungs and PaO 2 was less than 10 kPa (75 mmHg) or oxygen saturation was below 90% at FiO 2 1.0.…”
Section: Lung Injury Model (Ii Iii)mentioning
confidence: 99%
“…Pressure-regulated, volume-controlled (volume-preset) ventilation (PRVC) has been recently proposed as a new mode in which the smallest level of positive pressure required to deliver the preset tidal volume (V T ) is provided by the ventilator [6]. Mechanical breaths are in fact pressure-controlled; the level of PIP is regulated by microprocessor on a breath-by-breath basis to maintain the preset tidal and minute volumes.…”
Section: A Piotrowski W Sobala P Kawczyń Skimentioning
confidence: 99%